2009
DOI: 10.1037/a0015526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of emotional valence and arousal upon memory trade-offs with aging.

Abstract: Attention can be attracted faster by emotional relative to neutral information, and memory also can be strengthened for that emotional information. However, within visual scenes, often there is an advantage in memory for central emotional portions at the expense of memory for peripheral background information, called an emotion-induced memory trade-off. The authors examined how aging impacts the trade-off by manipulating valence (positive, negative) and arousal (low, high) of a central emotional item within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
95
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 63 publications
(101 reference statements)
16
95
2
Order By: Relevance
“…The neurobiology of the EEM has been the focus of much research, and it has been demonstrated that the amygdala plays an important role in the processing of emotional information and thus EEM [1,52,53,54]. Amygdala activity during the encoding of emotionally salient stimuli is predictive of subsequent memory [53], and damage to the amygdala abolishes the EEM [55].…”
Section: Discussionmentioning
confidence: 99%
“…The neurobiology of the EEM has been the focus of much research, and it has been demonstrated that the amygdala plays an important role in the processing of emotional information and thus EEM [1,52,53,54]. Amygdala activity during the encoding of emotionally salient stimuli is predictive of subsequent memory [53], and damage to the amygdala abolishes the EEM [55].…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have argued that, by narrowing the scope of attention to central information, negative emotional arousal (rather than emotional arousal generally or positive emotion) leaves people susceptible to memory errors concerning peripheral details (Berntsen, 2002;Waring & Kensinger, 2009; also see Porter, Taylor, & ten Brinke, 2008). For instance, people remembering negative photographs had fewer false memories about central details of the images, but more false memories about peripheral details, than people remembering positive or neutral photographs (Van Damme & Smets, 2014).…”
Section: Emotional Valence and Memorymentioning
confidence: 99%
“…1). The stimulus set included items and backgrounds used in prior studies (Kensinger, Gutchess, & Schacter, 2007a, b;Waring & Kensinger, 2009;Waring, Payne, Schacter, & Kensinger, 2010). Care was taken to make sure that the positive, negative, and neutral items were of comparable size and were balanced by approximate scene location.…”
Section: Methodsmentioning
confidence: 99%